Progress in optics. - Wolf, Emil (Progress in optics, 2009)
In the forty-eight years that have gone by since the first volume of Progress in Optics was published, optics has become one of the most dynamic fields of science. The volumes in this series which have appeared up to now contain more than 300 review articles by distinguished research workers, which have become permanent records for many important developments. - 3D optical microscopy - Transformation optics and geometry of light - Photorefractive solitons - Stimulated scattering effects - Optical vortices and polarization singularities - Quantum feedforward control of light.